Producing Enhanced Yield and Nutritional Pigmentation in Lollo Rosso Through Manipulating the Irradiance, Duration, and Periodicity of LEDs in the Visible Region of Light - Cammarisano, Laura; Donnison, Iain S.; Robson, Paul R. H. (Frontiers in Plant Science, 2020)
Pigmented food are an important part of the human diet and anthocyanins have demonstrable protection against tumour production in mouse models and beneficial effects on human liver chemistry. As such producing pigmented crops is important for a nutritionally diverse diet. Lollo rosso lettuce is a fast-growing pigmented plant, rich in phenolic compounds and represents a suitable system to test optimisation strategies for yield and anthocyanin production. High energy UV wavebands are often used to stimulate increased pigmentation; however, we hypothesised that optimising visible wavebands would deliver both yield and quality improvements. Growing Lollo rosso under irradiances between 5 and 180 Wm-2 using visible waveband LEDs produced 0.4 g fresh weight per Wm-2 in the linear portion of the curve between 5 and 40 Wm-2 and achieved an approximate asymptote of 20 g fresh weight at around 100 -120 Wm-2 for yield. Anthocyanin content increased linearly with irradiance. We attempted to optimise the visible wavebands by supplementing half the asymptotic energy for 15 days with supplemental red (R) or blue (B) wavebands in the peaks of photosynthetic activity (430-460 and 630-660 nm). R and B affected rosette morphology with no significant impact on yield but B significantly increased anthocyanin content by 94% compared to R. We therefore focussed on further optimising B by shortening the daily duration of supplemental B. The minimum B treatment that lacked significant pigment induction was 1 hour. We hypothesised that short durations would be more active at different times in the diurnal cycle. Supplemental B was applied for 2 hours at 4 different times. A night-break with B produced the highest yield and anthocyanin content. Our research demonstrates new ways to efficiently use readily available LEDs within the PAR wavebands to increase both yield and crop quality in controlled environment agriculture.